Preventive effect of sodium bicarbonate Ringer’s solution on post-contrast acute kidney injury in patients undergoing percutaneous coronary intervention - Liu, Jialin; Zhao, Wen; Feng, Baobao; Meng, Chong; Shang, Deya (Frontiers in Pharmacology, 2025)
BackgroundPost-contrast acute kidney injury (PC-AKI) is a common complication of coronary angiography (CAG) and percutaneous coronary interventions (PCI). Sodium bicarbonate Ringer’s solution (BRS) has been shown to reduce the incidence of postoperative AKI and the risk of acid-base disorder in surgical and critically ill patients. There is no research data of BRS in the field of PC-AKI. Therefore, this study aimed to evaluate the efficacy and safety of BRS in the prevention of PC-AKI.MethodsPatients with coronary atherosclerotic heart disease and stage 2–3b chronic kidney disease (CKD) who underwent CAG or PCI were prospectively enrolled and randomly assigned to BRS group or normal saline (NS) group from February 2024 to October 2024. The patients were given BRS or NS for hydration at 1mL/kg/h from 3 h before to 4 h after CAG/PCI. Serum creatinine (Scr), cystatin C (Cys-C) and neutrophil gelatinase-associated apolipoprotein (NGAL) were measured within 3 days before and 48 h after iodinated contrast agent exposure. The primary endpoint was PC-AKI, and the secondary endpoints were the need of renal replacement therapy (RRT) and major adverse cardiovascular events (MACEs) within 30 days after CAG/PCI. The correlation between BRS and PC-AKI was analyzed by multivariate logistic regression.ResultsThe baseline characteristics of patients in the two groups were similar, and the changes of Cys-C, NGAL, and electrolytes before and after CAG/PCI were not statistically significant. PC-AKI occurred in 1 patient (1.3%) in BRS group and 7 patients (9.3%) in NS group, and the difference was statistically significant (P = 0.029). Multivariate logistic regression showed that there was an approaching statistical trend of BRS to reduce the incidence of PC-AKI (P = 0.054).ConclusionBRS might be more suitable than NS in reducing the incidence of PC-AKI for patients with mild-to-moderate renal dysfunction who underwent CAG/PCI.